Functionalized polypropylenes as efficient dispersing agents for carbon nanotubes in a polypropylene matrix; application to electromagnetic interference (EMI) absorber materials - Thomassin, Jean-Michel; Huynen, Isabelle; Jerome, Robert; Detrembleur, Christophe (Polymer (Guilford), 2010)
Carbon nanotubes (CNTs) have been dispersed within polypropylene with the purpose to prepare electromagnetic interference (EMI) absorbers. In order to limit the reflectivity of the electromagnetic waves at the interface of the materials while achieving good absorbing properties, the CNTs concentration must be kept low (<3 wt%) which means that a perfect dispersion must be ensured. Since CNTs do not disperse well within apolar polymer matrices such as polypropylene, two compatibilizers bearing aromatic moieties, i.e. pyrene and pyridine, able to develop π-π interactions with the CNTs have been synthesized starting from polypropylene grafted by maleic anhydride (PP-g-MA). A masterbatch is first prepared by dispersion of CNTs within the compatibilizers by melt-mixing and coprecipitation followed by further dispersion within the PP matrix. Rheological and electromagnetic characterizations of the nanocomposites have demonstrated the efficiency of these compatibilizers to promote the dispersion of CNTs in PP and the good EMI shielding effectiveness of the PP matrix at a low CNTs concentration (2 wt%). [Display omitted]